2016
DOI: 10.1007/s00167-016-4130-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the influence of anaesthesia on the clinical and quantitative assessment of the pivot shift: a multicenter international study

Abstract: Prospective comparative study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…On the other hand, when patients were under anesthesia, there was a significant difference in posterior tibial acceleration [45]. Similarly, Lopomo et al found significant differences in acceleration and anteroposterior translation when comparing awake and anesthetized patients [46]. Consequently, it is fair to assume that examinations performed under general anesthesia are more precise in the determination of rotatory knee laxity in patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when patients were under anesthesia, there was a significant difference in posterior tibial acceleration [45]. Similarly, Lopomo et al found significant differences in acceleration and anteroposterior translation when comparing awake and anesthetized patients [46]. Consequently, it is fair to assume that examinations performed under general anesthesia are more precise in the determination of rotatory knee laxity in patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of a multicenter, prospective, observational cohort study, the Prospective International Validation of Outcome Technology (PIVOT) trial, at 4 international centers using a published study protocol. 20,26 Patients between 14 and 50 years of age who presented with a primary ACL injury and underwent surgery between December 2012 and February 2015 were included. Further inclusion criteria were at least 1 injured ACL bundle (evaluated on MRI) with surgery performed within 1 year of injury.…”
Section: Methodsmentioning
confidence: 99%
“…With the patient under general anesthesia, a standardized pivot-shift test was performed at all centers preoperatively in the operating room ( Figure 2 ). 20 The pivot-shift test was repeated with nonsterile devices immediately after surgery with the patient still in the operating room and under general anesthesia. Both times, the pivot-shift test was performed on the injured and contralateral healthy sides by an experienced orthopaedic surgeon to determine the side-to-side difference.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations